Osteogenesis imperfecta: Ultrastructural and histological findings on examination of skin revealing novel insights into genotype-phenotype correlation. (3rd March 2016) - Balasubramanian, M.; Sobey, G. J.; Wagner, B. E.; Peres, L. C.; Bowen, J.; Bexon, J.; Javaid, M. K.; Arundel, P.; Bishop, N. J.
ABSTRACT: Osteogenesis imperfecta (OI) is a heterogeneous group of inherited disorders of bone formation, resulting in low bone mass and an increased propensity to fracture. Over 90% of patients with OI have a mutation in COL1A1/COL1A2, which shows an autosomal dominant pattern of inheritance. In-depth phenotyping and in particular, studies involving manifestations in the skin connective tissue have not previously been undertaken in OI. The aims of the study were to perform histological and ultrastructural examination of skin biopsies in a cohort of patients with OI; to identify common and distinguishing features in order to inform genotype-phenotype correlation; and to identify common and distinguishing features between the different subtypes of OI. As part of the RUDY (Rare Diseases in Bone, Joints and/or Blood Vessels) study, in collaboration with the NIHR Rare Diseases Translational Research Collaboration, we undertook a national study of skin biopsies in patients with OI. We studied the manifestations in the skin connective tissue and undertook in-depth clinical and molecular phenotyping of 16 patients with OI. We recruited 16 patients: analyses have shown that in type 1 collagen mutation positive patients ( COL1A1/ COL1A2 ) (n-4/16) consistent findings included: variable collagen fibril diameter (CFD) and presence of collagen flowers. Histological examination in these patients showed an increase in elastic fibers that are frequently fragmented and clumped. These observations provide evidence that collagen flowers and CFD variability are consistent features in OI due to type 1 collagen defects and reinforce the need for accurate phenotyping in conjunction with genomic analyses.